2022
DOI: 10.1002/ntls.20210047
|View full text |Cite
|
Sign up to set email alerts
|

Consecutively fused single‐, double‐, and triple‐expanded helicenes

Abstract: We report the quantitative, chemoselective, and diastereospecific formation of the defect-free C-shaped single and S-and M-shaped consecutively fused doubleand triple-expanded homochiral helicenes (all-right (P) or all-left (M) handed), in which two and three expanded helicene subunits were exclusively fused together in a helically winding manner, respectively, through the trifluoroacetic acid-promoted intramolecular multistep cascade alkyne benzannulations of anthracene-based cyclization precursors composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…The modulation of helicene opto-electronic properties can be envisaged by two means: i. via the introduction of one or more heteroatoms in the π-conjugated structure, resulting in heterohelicenes such as phosphahelicenes, azahelicenes, borahelicenes and silicahelicenes with strongly modified chiroptical response compared to carbohelicenes; 10 ii. by enhancing their specific chiroptical properties through the design of multiple helicenes 11 or π-extended systems, 12 thereby promoting large π-electron delocalization and affording unique optoelectronic properties. However, the increase in the number of fused aromatic rings may give rise to solubility issues and limit their study to organic media exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation of helicene opto-electronic properties can be envisaged by two means: i. via the introduction of one or more heteroatoms in the π-conjugated structure, resulting in heterohelicenes such as phosphahelicenes, azahelicenes, borahelicenes and silicahelicenes with strongly modified chiroptical response compared to carbohelicenes; 10 ii. by enhancing their specific chiroptical properties through the design of multiple helicenes 11 or π-extended systems, 12 thereby promoting large π-electron delocalization and affording unique optoelectronic properties. However, the increase in the number of fused aromatic rings may give rise to solubility issues and limit their study to organic media exclusively.…”
Section: Introductionmentioning
confidence: 99%
“…Yashima and co-workers have shown that fusing multiple helical anthracenes together also effectively enables the separation of enantiomers, but these multiple helicenes display inferior |g abs | of ≤0.015. 32 Notably, the original expanded helicenes illustrated in Figure 1a have larger diameters than helical anthracenes (∼13.5 vs ∼11.5 Å), suggesting that they should show further improvement in |g abs |; however, a similar noncovalent locking strategy was attempted on such an expanded helicene that failed to provide configurational stability. 33 Lengthening the helicene backbone also increases ΔG ‡ e , but this poses a considerable synthetic challenge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This compound displayed a maximum CD dissymmetry factor, | g abs |, of 0.024 at 352 nm, supporting the theory that expanded helicenes should display superior chiroptical properties. Yashima and co-workers have shown that fusing multiple helical anthracenes together also effectively enables the separation of enantiomers, but these multiple helicenes display inferior | g abs | of ≤0.015 . Notably, the original expanded helicenes illustrated in Figure a have larger diameters than helical anthracenes (∼13.5 vs ∼11.5 Å), suggesting that they should show further improvement in | g abs |; however, a similar noncovalent locking strategy was attempted on such an expanded helicene that failed to provide configurational stability …”
Section: Introductionmentioning
confidence: 99%
“…Later, Yashima et al reported the facile synthesis of several consecutively fused expanded helicenes (D) through the trifluoroacetic acid-promoted intramolecular multistep cascade alkyne benzannulations. 8 Notably, the triple-expanded helicene (n=3) showed persistent chirality with the absorption and luminescence dissymmetry factors of up to 1.5 × 10 −2 (|gabs|) and 0.94 × 10 −2 (|glum|), respectively. These studies imply promising chiroptical properties of expanded helicenes but the synthesis of even longer expanded helicenes remains very challenging.…”
Section: Introductionmentioning
confidence: 99%